2008
DOI: 10.1080/87565640802418662
|View full text |Cite
|
Sign up to set email alerts
|

A Multidisciplinary Approach to Understanding Developmental Dyslexia Within Working-Memory Architecture: Genotypes, Phenotypes, Brain, and Instruction

Abstract: A unifying theoretical framework of three working memory components provides a systems perspective for discussing past and new findings in a 12-year research program that point to heterogeneity in the genetic and brain basis and behavioral expression of dyslexia: (a) codes for word-form storage and processing, (b) time-sensitive phonological and orthographic loops for maintaining information in working memory or outputting it, and (c) executive functions for language (e.g., rapid automatic switching of attenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
118
1
4

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(127 citation statements)
references
References 84 publications
4
118
1
4
Order By: Relevance
“…By adding working memory to our model, we were able to control for the working memory component in the phonological awareness task. Our results provided evidence for the argumentation of Berninger et al (2008) that the level of word reading efficiency in children with dyslexia is associated with both phonological awareness problems and working memory. The variation in working memory thus accounts for part of the relation between phonological awareness and word reading efficiency.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…By adding working memory to our model, we were able to control for the working memory component in the phonological awareness task. Our results provided evidence for the argumentation of Berninger et al (2008) that the level of word reading efficiency in children with dyslexia is associated with both phonological awareness problems and working memory. The variation in working memory thus accounts for part of the relation between phonological awareness and word reading efficiency.…”
Section: Discussionsupporting
confidence: 84%
“…This apparent difference in phonological awareness impairments may partly be due to the increased demand on working memory in more complex phonological awareness tasks (Berninger, 2008). Children with dyslexia show deficits in their working memory, phonological awareness, and word reading efficiency (Berninger, Raskind, Richards, Abbott, & Stock, 2008; Brosnan et al, 2002; Swanson, Zheng, & Jerman, 2009). Working memory predicts both phonological awareness and word reading efficiency (de Abreu, Gathercole, & Martin, 2011; Berninger, Abbott, Vermeulen, & Fulton, 2006; Christopher et al, 2012; Locascio, Mahone, Eason, & Cutting, 2010; Ramscar & Gitcho, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to a phonological deficit and accompanying working memory problems, children with dyslexia have problems with learning from text (e.g., Berninger, Raskind, Richards, Abbott, & Stock, 2008; Swanson, Zheng, & Jerman, 2009). Multimedia may support their learning by replacing written text with audio or by adding audio to the written text.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a longitudinal developmental study showed that both orthographical and phonological skills accounted for independent variance in later orthographic skills (Sprenger-Charolles et al 2003). It has been also suggested that both the orthographic and phonological measures contribute to distinguishing various types of dyslexia (Berninger et al 2008;Coltheart et al 2001;Hultquist 1997;Plaut et al 1996); although dyslexia has been strongly associated with a deficit in phonological processing (Ramus et al 2003;Shaywitz and Shaywitz 2005), reading disabilities may also be linked to problems with orthographic processing. We thus incorporated both orthographical and phonological measures into our reading and writing tests, with the expectation that their inclusion might help us distinguish not only various types of dyslexia but also dyslexia and ADHD.…”
Section: Introductionmentioning
confidence: 99%